If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + 5) = 2 + -2x Reorder the terms: -3(5 + x) = 2 + -2x (5 * -3 + x * -3) = 2 + -2x (-15 + -3x) = 2 + -2x Solving -15 + -3x = 2 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -15 + -3x + 2x = 2 + -2x + 2x Combine like terms: -3x + 2x = -1x -15 + -1x = 2 + -2x + 2x Combine like terms: -2x + 2x = 0 -15 + -1x = 2 + 0 -15 + -1x = 2 Add '15' to each side of the equation. -15 + 15 + -1x = 2 + 15 Combine like terms: -15 + 15 = 0 0 + -1x = 2 + 15 -1x = 2 + 15 Combine like terms: 2 + 15 = 17 -1x = 17 Divide each side by '-1'. x = -17 Simplifying x = -17
| 12x^2+4x+15=0 | | 3(7r-12)=21r-6 | | 63+30t+3t^2=0 | | 4x+2.9=9.7 | | 7(x+1)=-2(x-4)+x | | 12k-3(2k-3)=45 | | -5y-15=7y+9 | | -5-15=7y+9 | | 2(1.6x)-1.33=-x+4.13 | | 4z+17=3z+4 | | 5-2x-4x=9 | | 27(2/3n) | | 500/3000 | | 7/3xb^4 | | y=-15-(-2)-(11-6) | | 2x^2y+4xy-58y=0 | | y=-20+30-40-(-50) | | (10-y)+y=3.09 | | y=x^3+2x^2-8x-5 | | (9+z)(5z+3)=0 | | 5x^3+40x^2+60x=0 | | Z=23 | | 2x-8+2=x-3+5 | | f(x)=x^3+2x^2-8x-5 | | 4x(2x-1)^1/2 | | n^2-19n+10=0 | | 7(3-z)6=-z | | 1/3x+2=1/6x+4/3 | | 3y=2x+b | | 3(x+7)-2x=3+2x | | Y=x^4-3x^2 | | 28=4b-3s |